Metabolic dysfunction in female mice with disruption of 5α-reductase 1. Issue 1 (January 2017) - Livingstone, Dawn E W; Di Rollo, Emma M; Mak, Tracy C-S; Sooy, Karen; Walker, Brian R; Andrew, Ruth
Abstract : 5α-Reductases irreversibly catalyse A-ring reduction of pregnene steroids, including glucocorticoids and androgens. Genetic disruption of 5α-reductase 1 in male mice impairs glucocorticoid clearance and predisposes to glucose intolerance and hepatic steatosis upon metabolic challenge. However, it is unclear whether this is driven by changes in androgen and/or glucocorticoid action. Female mice with transgenic disruption of 5α-reductase 1 (5αR1-KO) were studied, representing a 'low androgen' state. Glucocorticoid clearance and stress responses were studied in mice aged 6 months. Metabolism was assessed in mice on normal chow (aged 6 and 12 m) and also in a separate cohort following 1-month high-fat diet (aged 3 m). Female 5αR1-KO mice had adrenal suppression (44% lower AUC corticosterone after stress), and upon corticosterone infusion, accumulated hepatic glucocorticoids ( 27% increased corticosterone). Female 5αR1-KO mice aged 6 m fed normal chow demonstrated insulin resistance ( 35% increased area under curve (AUC) for insulin upon glucose tolerance testing) and hepatic steatosis ( 33% increased hepatic triglycerides) compared with controls. This progressed to obesity ( 12% increased body weight) and sustained insulin resistance ( 38% increased AUC insulin) by age 12 m. Hepatic transcript profiles supported impaired lipid β-oxidation and increased triglyceride storage. Female 5αR1-KO mice were also predisposed to develop high-fat diet-induced insulin resistance. Exaggerated predisposition to metabolic disorders in female mice, compared with that seen in male mice, after disruption of 5αR1 suggests phenotypic changes may be underpinned by altered metabolism of glucocorticoids rather than androgens.